Effect of educational intervention in reducing acculturative stress among new international postgraduate students in public universities in Malaysia - Aljaberi, Musheer Abdulwahid Abdo (2019)
With the increasing number of international students joining Malaysian universities, acculturative stress resulting from their attempts to adjust to the culture of the host country is one of the most challenging issues that affect their life in a general and academic career in particular. Therefore, it is necessary for international students to receive better orientation, education and culturally appropriate health services. Despite the importance of this research topic, a few studies have been conducted among international postgraduate students in Malaysian public universities and reported their experience of acculturative stress and adjustment difficulties to the host country. The main aim of the current study was to develop, implement and evaluate the effects of an educational intervention on the acculturative stress, adjustment and intention to drop out among new international postgraduate students joining Malaysian public universities in the first semester of their academic year of 2017/2018. The study adopted an experimental quantitative research approach, specifically a cluster randomized controlled trial design. A randomization method was employed to allocate the universities to the intervention group (five universities) and to the control group (five universities), and the students were randomly recruited for the two groups. The study used a valid and reliable questionnaire and the primary outcome is acculturative stress while the secondary outcomes are adjustment and intention to drop out of university. The data were collected at three-time points, baseline (Time 1) before the intervention and immediately post-intervention (Time 2) and three- month follow-up (Time 3). Finally, the data were managed and analyzed using descriptive statistics, chi-square, independent T-test (Mann-Witney U test) and General Estimating Equations (GEE) to evaluate the effect of the educational intervention. The results of the current study showed that at baseline, the majority of international postgraduate students (78.5 %) reported their experience of moderate levels of acculturative stress, while 12.1 % of them experienced a higher level. However, 50.96 % of the students were moderately going through social difficulties and 16.28 % of them experienced a higher level of such difficulties. Similarly, while 42.72 % of the participants experienced a moderate level of psychological adjustment and 30.65% of them reported their experience at a low level, 50.9 % of them held intentions to withdraw from the university. Moreover, there were no significant differences between the intervention and control groups in terms of the participants’ acculturative stress, adjustment and intention to drop out (P> 0.05) at the baseline. The results obtained from the GEE analysis indicated a significant difference between the intervention and control groups at the post-intervention and three-month follow up in terms of the participants’ acculturative stress, adjustment and intention to drop out. The results of the GEE analysis illustrated a statistically significant effect of the implemented educational intervention, time and group with time interaction on acculturative stress, adjustment and intention to drop out at the three-time points with the P value of < 0.01. Testing the model effect showed significant effects within groups across the three-time points, which called for further analysis of the differences within each group. The results revealed that the level of acculturative stress and intention to drop out of university reduced significantly within the intervention group from the baseline (T1) to post-intervention (T2 ), from the postintervention to the three-month follow up (T3) and from T1 to T3 (p < 0.001), while the socio-cultural and psychological adjustment increased significantly. For the control group, the level of acculturative stress and intention to drop out from university increased significantly from T1 to T2, from T2 to T3 and from T1 to T3 (p <0.001), whereas the socio-cultural and psychological adjustment significantly decreased. The results of the current study indicate that the educational intervention was effective in reducing the level of acculturative stress and intention to drop out and increasing the level of socio-cultural and psychological adjustment among new international postgraduate students in Malaysian public universities.